Training On Improving Training On Improving Health Cadres Capacity In Eradication of Tuberculosis Disease In Communities - Kusumawati, R Lia; Hasibuan, Mirzan; Lubis, Inke Nadia Diniyanti (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Tuberculosis (TB) is an important issue in public health, where Indonesia ranks second in the world after India and China. The discovery of TB suspects and cases through health facilities is very important, this makes the role of health cadres in the community in the discovery of TB suspects in their area. The purpose of this community service activity is to train health cadres in an effort to increase the capacity of knowledge about tuberculosis (TB). Health cadres in the PKK area of ​​Medan Tuntung District have not been exposed to special training in tuberculosis infectious diseases. The results of the training show that there is a significant difference between the knowledge of tuberculosis infectious disease before training (pre-test) compared to after training (post-test) (p value <0.05). The results of the pre-test scores showed that cadre knowledge before training was categorized as good as 12/30 (40%) and cadre knowledge increased after receiving special training on Tuberculosis which was categorized as good at 26/30 (87%).